Coupling microwave photons to a mechanical resonator using quantum interference - I. C. Rodrigues (Nature Portfolio, 2019)
Capacitive optomechanics in the microwave regime suffers from inherent and practical limitations on the maximum achievable coupling strength. Here, the authors demonstrate flux-mediated inductive optomechanical coupling allowing tunable single-photon coupling rates.